Invariants for the topological characterization of the iteration of differentiable functions – the bimodal case - Correia, Maria F. (2014)
We consider dynamical systems defined by a particular class of differentiable functions, as fixed state space. The dynamics is given by the iteration of an operator induced by a polynomial map which belongs to an appropriate family of isentropic bimodal interval maps. We characterize topologically these dynamical systems, in particular using the invariants defined for the iteration of the bimodal interval maps.